2014
DOI: 10.1186/1029-242x-2014-488
|View full text |Cite
|
Sign up to set email alerts
|

Some fixed point results for generalized contraction mappings with cyclic ( α , β ) -admissible mapping in multiplicative metric spaces

Abstract: The purpose of this work is to introduce new types of contraction mappings in the sense of a multiplicative metric space. Fixed point results for these contraction mappings in multiplicative metric spaces are obtained. Our presented results generalize, extend, and improve results on the topic in the literature. Moreover, our results cannot be directly obtained as a consequence from the corresponding results in metric spaces. We also state some illustrative examples to claim that our results properly generalize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…They established several xed point theorems in full multiplicative metric space, which laid the foundation for the idea of multiplicative contraction mapping. Please see [7,12,13,17,20] for further ndings on multiplicative metric space. ( [3-5, 7, 9-11, 15, 16, 18, 19, 21] and references therein) has applications for multiplicative calculus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They established several xed point theorems in full multiplicative metric space, which laid the foundation for the idea of multiplicative contraction mapping. Please see [7,12,13,17,20] for further ndings on multiplicative metric space. ( [3-5, 7, 9-11, 15, 16, 18, 19, 21] and references therein) has applications for multiplicative calculus.…”
Section: Introductionmentioning
confidence: 99%
“…Dnition 1.10. [17] Let A and B be nonempty subsets of a multiplicative metric space (X, d). A mapping T : A → B is said to be proximal contraction if there exists a nonnegative α ∈ [0, 1) such that, for all u, v, x, y in A, It can be observed that a best proximity point reduces to a xed point if the underlying mapping is a self-mapping.…”
Section: Introductionmentioning
confidence: 99%
“…Hxiaoju et al [24] studied common fixed points for weak commutative mappings on a multiplicative metric space (see also, [25]). Recently, Yamaod and Sintunavarat [26] obtained some fixed point results for generalized contraction mappings with cyclic (α, β)-admissible mapping in multiplicative metric spaces. In this paper, unique common coupled fixed point results for w * − compatible maps, which are more general than commuting and w− compatible mappings, are obtained in partially ordered multiplicative metric spaces, without exploiting the notion of continuity.…”
Section: Introductionmentioning
confidence: 99%
“…Later, Bhaskar and Lakshmikantham [4] proved a new fixed point theorem for a mixed monotone mapping in a metric space powered with partial ordered by using a weak contractivity type assumption. For more information about multiplicative metric space one can see the research papers in [5][6] and about coupled fixed point, see the research papers in [7][8][9][10][11] and references there in.…”
Section: Introductionmentioning
confidence: 99%